More‐than‐human emotions: Multispecies emotional labour in the tourism industry. Issue 1 (24th April 2019) - Dashper, Katherine
Abstract : The concept of emotional labour has been subject to critique, evaluation, development and extension over the last 35 years, but it remains firmly anthropocentric. This article begins to address this shortcoming by illustrating some of the productive potential of extending the concept of emotional labour to include more‐than‐human and multispecies perspectives. Organizations are not solely human phenomena, but research usually fails to consider the role of non‐humans in work in contemporary capitalism. Using the example of trail horses in tourism, I argue that some non‐human animals should be considered workers, and that they do perform emotional labour in service to commercial organizations. More‐than‐human and multispecies perspectives capture some of the complexities of everyday organizational practices, and can inform feminist research attuned to the experiences of marginalized others, human and non‐human.